Terapi Musik untuk Penurunan Nyeri Pada Pasien Post Op Sectio Ceasarea: : Literature Review - Ekalia Yulianti; Laily Mualifah (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: The World Health Organization (WHO) revealed that genesis Sectio Caesarea in a country is about 5-15%. Globally, the average Sectio Caesarea is 186% of the world's total birthrate. Sectio Caesarea is either the surgical process of bringing forth a fetus or the incision in the lining of the abdomen and uterus. Purpose :the study of the effects of music therapy on patients Post Op Sectio Caesarea. It is aimed at analyzing the effects of music therapy on reducing pain in patients Post Op Sectio Caesarea. Method :Research methods use the review literature by systematic review. Data gathering is done through Internet searches using Google schoolar with a keyword affecting music therapy. Results :The review contained five research journals that met the criteria for inclusion, with the average respondent affected by music therapy having a significant reduction in pain. Conclusion : The conclusion is, thus, the effect of music therapy on patients post op sectio caesarea decline in pain.